Determination of the formation mechanism of zinc and nickel layered double hydroxides - Kovalenko, Vadym; Borysenko, Anastasiia; Andreiev, Dmytro; Dopira, Anton; Demchenko, Oleksii; Kotok, Valerii; Medianyk, Volodymyr; Sukhomlyn, Dmytro; Shuklin, German; Verbitskiy, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study – the formation mechanism of Zn-Al nitrate, Zn-Al tripolyphosphate, Ni-Al carbonate and Ni(II)-Ni(III) carbonate layered-double hydroxides (LDHs). To calculate the composition of the precipitate at the LDH formation stage, the following hypotheses were proposed: 1) basic salt hypothesis (BSH): all cations completely precipitate, then OH- ions replace the anions; 2) variable cation composition hypothesis (VCCH): the precipitate is formed by a saturated "guest" cation, and subsequently the amount of the "host" cation increases. Potentiometric titration with a glass electrode was used to determine the LDH formation mechanism. A two-stage formation mechanism was observed for Zn-Al-NO3 LDH. At the first stage, aluminum hydroxide forms (pH = 6.47) via the formation of the hydroxo salt Al(OH)0,667(NO3)2,333 (pH = 4.98). At the second stage, LDH formation proceeds through intermediate stages: at pH = 7.36, the is composition Zn0,8Al0,2(OH)1,20(NO3)1,00 (BSH) or Zn0,667Al0,333(OH)2(NO3)1,667 (VCCH), at pH = 9.35, the composition is Zn0,8Al0,2(OH)1,93(NO3)0,27 (BSH) or Zn0,793Al0,207(OH)2(NO3)0,204 (VCCH). A two-stage mechanism is characteristic of Zn-Al-P3O10 LDH. At pH = 6.25, the hydroxo salt Al(OH)2,66(P3O10)0,067 is formed, whereas at pH = 9.25, LDH with the composition Zn0,8Al0,2(OH)2,00(P3O10)0,040 is obtained. For Zn-Al LDH, a pH range of 7–10 is recommended. It was found that during the formation of Ni-Al-CO3 LDH, the stage of Al hydroxocompound formation is absent due to the complete irreversible hydrolysis of Al3+ in the presence of At pH = 6.5, the precipitate Ni0,8Al0,2(OH)1,066(CO3)0,567 (BSH) or Ni0,624Al0,376(OH)2(CO3)0,376 (VCCH) is formed, which is transformed into LDH upon further alkalization. The synthesis of Ni-Al-CO3 LDH should be carried out at pH = 8–11. A single-stage formation mechanism is determined for Ni(II)-Ni(III)-CO3 LDH, with a recommended synthesis pH range of 10–11. Comparative analysis shows that the VCCH better describes the change in the precipitate composition during LDH formation